Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1029/2021ea001906
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Satellite Precipitation Products in Relation With Orographic Enhancement Over the Western United States

Abstract: Satellite-based precipitation estimates have been widely used in many research and application areas, including short-term weather and long-term climate prediction (Arkin & Ardanuy, 1989;Huffman et al., 1995). Precipitation estimates from satellite measurements are unique due to their global coverage, including oceanic and high terrain mountainous regions where ground-based observations are not always possible (Kidd et al., 2017). It is difficult to get broad spatial coverage in mountainous areas using rain ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
(95 reference statements)
0
3
0
1
Order By: Relevance
“…IMERG is a multisensor technique; its estimates represent a spatiotemporally averaged rainfall from multiple microwave estimates. Also, the accuracy of PMW rainfall retrievals over mountainous areas is affected by the orographic effect on cloud and rainfall formation (Adhikari and Behrangi 2022;Kumah et al 2021b;Petković and Kummerow 2017), which may explain the high differences observed between the RF versus IMERG and RF versus MPE estimates for areas with complex topography. Furthermore, the high spatiotemporal rainfall variability in the study area may also contribute to the differences in the rainfall estimates by the gauge, RF, IMERG and MPE (Wakachala et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…IMERG is a multisensor technique; its estimates represent a spatiotemporally averaged rainfall from multiple microwave estimates. Also, the accuracy of PMW rainfall retrievals over mountainous areas is affected by the orographic effect on cloud and rainfall formation (Adhikari and Behrangi 2022;Kumah et al 2021b;Petković and Kummerow 2017), which may explain the high differences observed between the RF versus IMERG and RF versus MPE estimates for areas with complex topography. Furthermore, the high spatiotemporal rainfall variability in the study area may also contribute to the differences in the rainfall estimates by the gauge, RF, IMERG and MPE (Wakachala et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Examining in detail the major inconsistencies and errors between the gauge measurements, IMERG daily products, and daily estimations corrected by applying blending models, it is possible to notice worse performances over the eastern region, which is poorly gauged (especially in the southeast corner) and characterized by high intensity and depth of rainfall [28] and diverse mechanisms of precipitation (i.e., orographic rather than cyclonic) that can be challenging to estimate accurately due to interactions with complex orography causing large spatial variations [81][82][83].…”
Section: Seasonality Analysismentioning
confidence: 99%
“…Sun et al, 2018), regional (Bytheway et al, 2023;Hu et al, 2016;Satgé et al, 2020), national (Aksu & Akgül, 2020;Du et al, 2022;Li et al, 2022;Liu et al, 2022;Nepal et al, 2021;W. Xie et al, 2022), and basin scales (Adhikari & Behrangi, 2022;Dangol et al, 2022;Gu et al, 2022;J. Chen et al, 2020;Khadka et al, 2022;Kumar et al, 2021;.…”
Section: Introductionunclassified
“…Until now, many evaluation studies of such datasets have been conducted at global (Beck et al., 2017; Derin et al., 2019; Li et al., 2021; Q. Sun et al., 2018), regional (Bytheway et al., 2023; Hu et al., 2016; Satgé et al., 2020), national (Aksu & Akgül, 2020; Y. Chen et al., 2021; Du et al., 2022; Li et al., 2022; Liu et al., 2022; Nepal et al., 2021; Sharma, Khadka, et al., 2020; W. Xie et al., 2022), and basin scales (Adhikari & Behrangi, 2022; Dangol et al., 2022; Gu et al., 2022; J. Chen et al., 2020; Khadka et al., 2022; Kumar et al., 2021; W. Wang et al., 2020). Most of them have uncovered uncertainties in the measurements, particularly when dealing with complex terrain.…”
Section: Introductionmentioning
confidence: 99%